PENGARUH RETURN ON INVESTMENT (ROI), CASH RATION, DEBT TOTAL ASSET, EARNING PER SHARE (EPS) DAN SIZE ATAS DIVIDEN KAS (STUDI PADA EMITEN MANUFAKTUR DI BURSA EFEK JAKARTA) - jen, Surya (Fakultas Ekonomi Universitas Muhammadiyah Aceh, 2011)
The objective of this research is to examine and analyze the influence of return on investment (ROI), cash ratio, current ratio, debt to total asset (DTA), earning pershare (EPS), and size as independent variabel to dividen kast as dependent variabel both simultaneously an partially in manufacturing companies listed in Jakarta stock exchange (JSX). Observation periods from 2001 until 2005. The type of research used in verification research or research to verify hypothesis with simple random sampling. The object of population are manufacturing industries which listed in Jakarta Stock Exchange (JSX) that it’s financial statement has information about return on investment (ROI,) cash ratio, current ratio, debt to total asset (DTA), earning pershare (EPS), size and paid to dividen kast. The research samples 21 manufacturing corporation. To aimed influence of independent variable to dependent variable both simultaneously and partially use multiple regression. Result of this research show that; (1) ROI has no significant influence on dividen kast, (2) cash ratio has no significant influence on dividen kast, (3) current ratio has significant influence on dividen kast, (4) DTA has no significant influence on dividen kast, (5) EPS has a significant influence on dividen kast,(6) size has no significant influence on dividen kast, (7) simultaneously ROI, Cash ratio, current ratio, DTA, EPS and size has a significant (72%) influence on dividen kast. Keywords: return oninvestment (ROI), Cash ratio, current ratio, debt to total asset (DTA),earning per share ( EPS), size and dividen kast. DAFTAR PUSTAKA Algifari (2000), Analisis Regresi: Teori, Kasus dan Solusi, Edisi 2, BPFE,Yogyakarta. Bringham F. Eugene (2000), Manajemen Keuangan , Edisi 8, Erlangga. Edi Susanto (2001). “ Analisis Faktor- Faktor yang mempengaruhi Kebijakan Dividen Di BEJ Periode 1999”. Eduardus Tandelilin, Analisis Investasi dan Manajemen Portofolio, BPFE, Yogyakarta. Erich. A. Helfert, Analisis Laporan Keuangan, Edisi7, Erlangga, Jakarta,1993. Indonesian Capital Market Directory 2001 Indonesian Capital Market Directory 2003 Indonesian Capital Market Directory 2004 Jogiyanto, Teori Portofolio dan Analisis Investasi, BPFE UGM , Jogjakarta,1998. Mutamimah dan Sulistyo. (2000).”Analisis Faktor-Faktor yang mempengaruhi Dividen Per Share Perusahaan-Perusahaan yang Go Public di Bursa Efek Jakarta”. Niniek Dwi Puspitowati (1998), Pengaruh Pengumuman Pembagian Dividen Tunai Terhadap Aktivitas Volume Perdagangan Saham di BEJ, Tesis, Universitas Gajah Mada, Yogyakarta. Robbert Ang (1997), Buku Pintar: Pasar Modal Indonesia, Mediasoft Indonesia. Sawidji Widoadmodjo (1996), Cara Sehat Investasi di Pasar Modal, PT Jurnalindo Aksara Grafika, Jakarta. Sri Rahayu (2004), Belajar Mudah SPSS Versi 11.05, Alfabeta, Bandung. Sritua Arief, Metodologi Penelitian Ekonomi, Penerbit Universitas Indonesia, Jakarta, 1993. Suad Husnan (1994), Dasar Teori Portofolio dan Analisis Sekuritas, Edisi 2, AMP YKPN, Yogyakarta. Sugiyono, Statistika Untuk Penelitian, Alfabeta, Bandung,2001. Sumarmo (1990), Pengantar tentang Pasar Modal di Indonesia, Penerbit Balai Aksara, Yudistira dan Pustaka Saadiyah. Sunarto dan Andi Kartika, Analisis Faktor- Faktor yang mempengaruhi Dividen Kas di BEJ, Jurnal Bisnis dan Ekonomi, Vol. 10, No.1:67-82, 2003. Tri Harsini Wahyuningsih, Dividen Cut: Satu Alternatif Dalam Kebijakan Dividen, Jurnal Bisnis dan Ekonomi, Vol 10, 2000. Yuniningsih, Interdependensi Antara Kebijakan Dividen Payout Ratio, Financial Leverage, dan Investasi pada Perusahaan manufaktur yang Listed di Burs Efek Jakarta, Jurnal Bisnis dan Ekonomi, Vol. 9, No.2: 164-182, 2001.